Evaluación in vitro e in vivo de combinaciones de drogas y nuevas drogas con potencial para el tratamiento de la enfermedad de Chagas - Gulin, Julián Ernesto Nicolás (2019)
Chagas disease is an anthropozoonosis caused by the protozoan Trypanosoma cruzi (T. cruzi), and it is endemic in the Americas, affecting approximately 10 million people,\ncausing nearly 10,000 deaths per year due to cardiovascular or gastrointestinal\ncomplications.\nAvailable drugs, nifurtimox and benznidazole, are associated with a relatively high frequency of adverse events, the most common being nausea, anorexia, headache,\ngastrointestinal discomfort and arthralgias. It is also common for the appearance of erythema and pruritus. These effects added to the prolonged duration of treatment (up to 2 months) and the perception of moderate effectiveness during the chronic phase\nare frequent causes of treatment discontinuation.\nIn this context, searching for new safe and accessible therapeutic alternatives for\nChagas disease treatment is a pending objective.\nThere is little interest by the pharmaceutical industry on research and development of drugs for Chagas disease, mainly due to the socioeconomic characteristics of the\naffected population. The repositioning or reorientation of drugs and combinatorial\ntherapy arise as alternatives to the development of new molecules and involve a\nsignificantly lower investment of resources.\nIn this work, available drugs for clinical use were selected and were evaluated by in\nvitro and in vivo methods to determine anti-T. cruzi activity of drugs candidates.\nThirty-eight drugs were evaluated in vitro on trypomastigote and amastigote stages\nwith a low-throughput screening system using the T. cruzi VD strain, previously\ncharacterized. Also, a high-throughput screening system was standardized and optimized with the Dm28c/pLacZ strain, with which other thirty-eight drugs were evaluated. From these results, five drugs (nitazoxanide, pyrimethamine, ivermectin\nvoriconazole, and miltefosine) were evaluated in a murine model of acute infection with T. cruzi.\nThe trypanocidal or trypanostatic effects of the drugs studied confirmed the anti-T. cruzi activity of the drugs available for clinical use, validating the repositioning strategy to\nidentify new candidate compounds for the treatment of Chagas disease.\n